Quality of selected aromatic herbal drugs available on Belgrade's marketplaces - Drobac Milica; Arsenijević Jelena; Stojanović Danilo; Jančić Radiša; Kovačević Nada (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2017)
Herbal drugs are often administered in the form of monocomponent teas or herbal tea mixtures (tea blends). In order to assess the quality of herbal drugs that are components of the monocomponent teas commercially available on marketplaces in Belgrade, we analyzed 4 samples of Melissa leaf (Melissae folium), 6 samples of Wild thyme, (Serpylli herba), 6 samples of Yarrow (Millefolii herba), 4 samples of Wormwood (Absinthii herba) and 6 samples of Juniper (Juniperi pseudo-fructus), according to the procedures given in European Pharmacopoea. Macroscopic and microscopic features of investigated herbal drugs, as well as their TLC profiles, were in agreement with corresponding data described in Ph. Eur. One sample of Melissa leaf, one sample of Wild thyme and two samples of Juniper, did not fullfil the requirements of general tests. Due to inappropriate size of cut, test on foreign matter could not be performed for some samples. Concerning specific quality, all samples of Melissa leaf, Wild thyme, Wormwood and Juniper were in accordance with Ph. Eur. Regarding the content of essential oil, Yarrow samples met the requirements of Ph. Eur., but the proazulenes content in five samples was lower than required. In conlcusion, the results of these analyses point to high medicinal potential of the most herbal drugs studied. On the other hand, unsatisfying general quality and inappropriate size of cut of several samples could be related to inadequate processing and handling of plant material.